HUBUNGAN PENGETAHUAN DENGAN SIKAP KELUARGA MERAWAT KLIEN DALAM MENGENDALIKAN HALUSINASI DI UNIT POLIKLINIK JIWA A (UPJA) RSJ. PROF. HB. SA’ANIN PADANG - Dian Rahmi (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Healing and relapse in patients with hallucinations or strongly influenced by therole of family support in caring for the client to control hallucinations. Frequentrecurrence impact on clients hallucinations and downs client psychological condition. Thepurpose of this study to examine the relationship of knowledge families caring for clientswith family attitude in controlling hallucinations in Unit A Soul Clinic (UPJA) RSJ. Prof.HB. Sa'anin PadangThis research is a descriptive analytic cross sectional type. The population was916 with a sample of 90 families who had taken hallucinogenic clients with accidentalsampling. Study used a questionnaire instrument. Data were analyzed using univariate andbivariate statistical test Chi Square.The results showed 53.3% of respondents had low knowledge about caring forclients hallucinations, 61.1% of respondents had a negative attitude in treating clientshallucinations. Results of the bivariate analysis with p value = 0.025 shows that there is asignificant relationship between the level of knowledge of thefamily with the family in caring for clients attitude hallucinations. Based on these results itcan be concluded that knowledge influence the attitude of the family in caring for clientshallucinations.Keywords: Knowledge, Attitude, Hallucinations.